History, miscegenation and identity. Ethnocultural miscegenation as totalizing essentialism - Ramón Ojeda, Rafael (2019)
The historical and natural process of ethnocultural miscegenation, after its gradual stabilization as a mestizo subjectivity during the 20th century, a process that began during the 16th century with the arrival of the Spanish in Peruvian lands, has become the main reference for the idea. of Peruvian nationality and identity, establishing itself as a hybrid entity that would summarize all the alternative and possible subjectivities of Peru, until imposing itself as a hegemonic social group, resulting from that long process of de-cruising and cholification of the country, a country whose identity pattern has been facing the national symptoms of segregation, discrimination and racism, with the symbolic utopia of miscegenation as a positive post-racial context, but which, by becoming a nationalist ideological slogan imposed as a basic reference of an authentically Peruvian identity, will become a totalizing and totalizing ethnocultural homogenization project litarian, because it goes on to cover up the ethnocultural asymmetries and flaws of a country.